Economic Analysis of Paddy Rice Production in Niger Delta Region of Nigeria - F. A, Kadiri; C. C, Eze; J. S, Orebiyi; A, Henri–Ukoha (Asian Journal of Agriculture and Rural Development, 2014)
The study examined economic analysis of paddy rice production in Niger Delta Region of Nigeria in view to determine how profitable the crop is in the study area and how inputs or resources used in paddy rice production significantly affect the crop’s production. The data for the study was collected from 300 rice farmers in three out of nine states in the region based on their intensity in rice production in the study area using multistage and simple random sampling technique. Data analysis was carried out using descriptive statistics, multiple regression model and profitability model. Rice production was found to be profitable as farmers realized ₦300,071.84 as Net farm Income. It was also found that resources used in paddy rice production significantly affect paddy rice production. The result indicated that mean age of paddy rice farmers was 49 years, the mean farming experience was 17 years while mean cultivated land was 2.32 hectares It was recommended that Reviewing the Land Use Act of 1990 is critical so that most of the fertile land held by government will be released to rice farmers, also providing skilled labour required in rice production and easy evacuation of farm produce will go a long way in increasing the production of paddy rice in the study area.